CFD based investigations for the design of severe service control valves used in energy systems. (1st December 2017) - Asim, Taimoor; Charlton, Matthew; Mishra, Rakesh
Graphical abstract: Highlights: Flow coefficient determination for different valve components. Local flow characteristics in a severe service control valve. Development of a prediction model for the local flow capacity of the trim. Abstract: Multistage severe service control valves are extensively used in various energy systems, such as oil & gas, nuclear etc. The primary purpose of such valves is to control the amount of fluid flow passing through them under extreme pressure changes. As opposed to the conventional valves (butterfly, gate etc.), control valves are often installed in energy systems with geometrically complex trims, comprising of various geometrical features, formed by a complex arrangement of cylindrical arrays. The pressure within the trim varies in controlled steps and hence, cavitation resistance can be embedded in the trim through improved design process for the trim for severe service applications in energy systems. The flow characteristics within a control valve are quite complex, owing to complex geometrical features inherent in such designs, which makes it extremely difficult to isolate and quantify contribution of these features on the flow characteristics. One of the most important design parameters of such trims is the flow coefficient (also known as flow capacity) of the trim which depends on the geometrical features of the trim. The design of valves for particular performance envelop within the energy systems depends on effects of complex trim geometrical features on performance characteristics; hence, the focus of recent research is on quantifying the hydrodynamic behaviour of severe service control valves, including the trims. This includes the estimation of the local flow capacity contributions of the geometrical features of the trim through detailed numerical investigations. In this work, a tool has been developed that can be used to predict the local contribution of geometrical features on the flow coefficient of the trim. It is expected that this work will result in better performance of the energy systems where these valves are used.